Authoritarianism and Free Markets: Notes on Fascism, Populism, and Economics - Finchelstein, Federico (Social research, 2024)
Is there a link between authoritarian politics and free market economics? How important has economic theory been historically to the rise of authoritarian systems and ideologies? Are fascism and populism determined by economic priorities or economic interests? In this article, I argue that economics was not that important, and certainly not as important as politics was, for fascists and populists. I then address how this is changing in the present cases of wannabe fascist populists such as Donald Trump in the United States and Javier Milei in Argentina.